Fishery policies and economies, 1957-1966 - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1970)
This book deals with the national fishery policies published by OECD in 1960.
oo 08/04/2019
Loans
Keywords: Fisheries; Fishery policy